2021
DOI: 10.7554/elife.67315
|View full text |Cite
|
Sign up to set email alerts
|

Canonical NF-κB signaling maintains corneal epithelial integrity and prevents corneal aging via retinoic acid

Abstract: Disorders of the transparent cornea affect millions of people worldwide. However, how to maintain and/or regenerate this organ remains unclear. Here, we show that Rela (encoding a canonical NF-kB subunit) ablation in K14+ corneal epithelial stem cells not only disrupts corneal regeneration but also results in age-dependent epithelial deterioration, which triggers aberrant wound healing processes including stromal remodeling, neovascularization, epithelial metaplasia, and plaque formation at the central cornea.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 67 publications
(80 reference statements)
0
16
0
Order By: Relevance
“…We reexamined NOTCH1 expression by western blot and found that NOTCH1 was expressed in mouse cornea samples, which was increased upon alkali-induced injury ( Figure 1 A). In this study, we briefly exposed the mouse cornea to NaOH so that the damage was limited to the epithelial layer with the underlying stroma unscathed ( Ma et al., 2006 ; Yu et al., 2021 ). The injured epithelial layer is recovered within 14 days ( Yu et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We reexamined NOTCH1 expression by western blot and found that NOTCH1 was expressed in mouse cornea samples, which was increased upon alkali-induced injury ( Figure 1 A). In this study, we briefly exposed the mouse cornea to NaOH so that the damage was limited to the epithelial layer with the underlying stroma unscathed ( Ma et al., 2006 ; Yu et al., 2021 ). The injured epithelial layer is recovered within 14 days ( Yu et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we briefly exposed the mouse cornea to NaOH so that the damage was limited to the epithelial layer with the underlying stroma unscathed ( Ma et al., 2006 ; Yu et al., 2021 ). The injured epithelial layer is recovered within 14 days ( Yu et al., 2021 ). We carried out immunohistochemical staining for Hes1, a downstream target of Notch signaling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, decreased expression of ALDH1A1 has been linked to the development of Parkinsons' disease [56]. Furthermore, the ALDH1A1 protein is a critical enzyme for maintaining clarity in human, rat, and mouse lenses, and corneal integrity; ALDH1A1-null mice grow to adulthood, but develop cataracts later in life (by six to nine months of age) [57][58][59][60]. Hematopoietic cells from ALDH1A1-deficient mice exhibit increased sensitivity to liver metabolites of cyclophosphamide; however, ALDH1A1 deficiency did not affect the basal function of stem cells from the hematopoietic and nervous system [61].…”
Section: Aldh1a1mentioning
confidence: 99%